Investigation of Hydrological Drought in Central Dry Zone, Myanmar - Poe Zar Ni Aung; Aye, Nilar; Yin Yin Htwe (AI Society & STMIK Indonesia, 2025)
This study presents the investigation of hydrological drought in Myanmar’s Central Dry Zone using the Streamflow Drought Index (SDI) across various timescales (3, 6, 9, and 12 months) to assess its impact on water resources and agricultural productivity. The Central Dry Zone, which includes the Ayeyarwaddy River and encompasses the regions of Sagaing, Mandalay, and Magway, shows significant vulnerability of hydrological extremes due to its semi-arid climate and dependence on water resources. Monthly discharge data from selected hydrological stations from 1993 to 2022 is analyzed using DrinC 1.7 software to derive SDI values and drought characteristics. The results show that critical drought events in 2005-2006, 2013-2015, and 2019-2021 for all stations are marked by high severity and extended duration. Short-term SDI (SDI 3 and SDI 6) values capture rapid, intense droughts, while long-term SDI (SDI 9 and SDI 12) highlight extended water shortages. From this result, Monywa station shows the highest severity and duration of droughts across all SDI timescales compared to other stations. The results underscore the necessity of strategic water management and drought mitigation measures to protect agriculture and guide planning, establish early warning systems, and support sustainable development in the Central Dry Zone, Myanmar.